Regulating Anti-Competitive Business Conduct via Competition Law in Malaysia - Haliza A Shukor; Nazura Abdul Manap (Faculty of Management & Muamalah, KUIS, 2024)
The introduction of the competition law in Malaysia via Competition Act 2010 has brought a tremendous shift in business practices. Common practice in businesses such as collusion to exploit quantity and price of goods in the market is no longer permitted with the coming into force the Competition Act 2010 in 2012. Hence, it is the aim of this paper to identify roles of Malaysia competition law in regulating anti-competitive business conduct in Malaysia. The result indicated that while competition law in Malaysia plays its role in combating anti-competitive business conduct, improvements of the provisions such as inclusion of specific merger provisions in the Competition Act 2010 and specific guidelines for intellectual property matters are needed in order to further support implementation of competition law in Malaysia. This paper employs library based approach which collects data from statutes, decided cases, journals and books.